Virulence genes and antimicrobial susceptibility of Escherichia coli taken from women with vaginitis in Talca, Chile - Carlos Padilla; Andrés Padilla; Olga Lobos (Journal of Infection in Developing Countries)
Introduction: Vaginitis is one of the most common reasons women visit a gynecologist. Escherichia coli has been isolated from women with vaginitis, but its role as a vaginal infection aetiological agent is controversial. This study aimed to detect virulence genes and determine the antimicrobial susceptibility of E. coli strains isolated from monomicrobial and polymicrobial cultures collected from women with  vaginitis. Methodology: The presence of the following virulence genes: papC, hly, iucC, afa, fimH, neuC, sfa/foc, cnf1, usp, and ibeA in two E. coli groups was determined by PCR. The antibacterial susceptibility of strains was tested. Results: A higher percentage (93.3%) of isolated strains from monomicrobial cultures with virulence genes in relation to  polymicrobial cultures (56.7%) was found. The most frequent virulence genes in both groups were hly (p = 0.0357), fimH (p = 0.000), and cfn1 (p = 0.000). In addition, E. coli isolated from monomicrobial cultures showed 5 genetic combinations compared to the 10 observed in the polymicrobial cultures. An increased number of strains were sensitive to cefotaxime, moxifloxacin, and ciprofloxacin. A high resistance to trimethoprim-sulfamethoxazole was observed. Conclusions: Most of the E. coli strains isolated from monomicrobial cultures and some from polymicrobial cultures showed virulence genes. A better understanding of  the virulence and antibacterial susceptibility of E. coli strains isolated from patients with vaginitis can contribute to improved diagnosis and treatment of this disease.